Model Pendidikan TasawufWalisanga Perspektif Teori-Teori Pendidikan - Sokhi Huda (TSAQAFAH, 2010)
Kidung Walisanga is a collection of Indonesian cultural heritage famous with Dhandang Gendis/Dhandang Gula. Dhandang ghendis Kidung Artati was authored by Walisanga as a medium of education and Islamic call that emphasizes the cultural basis of people as the objects. This is a kind of tasawuf education that consists of three elements: (1) concept of human being life journey, (2) journey to a perfect life, and (3) achieved result. The first two elements are got by mediation medium to utilize a pure energy in reaching a psychological effect, i.e. a purified sole and peaceful heart. While the third, emphasizes on pragmatic uses such as self protection from dangers and possessing supernatural heirloom. From linguistic perspective, kidung emphasizes on sanepan (metaphor) style. While from art perspective, it has a creative, individualization, and harmonization elements. From philosophical perspective, it has axiological values emphasizing pragmatic uses in the world. Beside all of that, there is an important element of tasawuf which is not included in kidung, i.e. guide role. Kidung, finally, is walisanga’s cultural approach model in education and Islamic call which is primarily based on community cultural basis, thus, kidung nuance shows a style fcultural Islam.